Argon Plasma Treatment at the i-/p-Interface in Silicon Thin-Film Solar Cells and its Influence on the Light Induced Degradation. (December 2015) - Neumüller, Alex; Sergeev, Oleg; Vehse, Martin; Agert, Carsten
Abstract: In thin-film silicon solar cells the p-doped layer and the i-/p-interface are most critical for the parasitic absorption and the electrical behavior of the solar cell. In this work, we present recent investigations of argon plasma treatment (APT) at the i-/p-interface in high efficient thin-film solar cells with hydrogenated amorphous silicon (a-Si:H) absorber in n-i-p configuration. Our experimental investigations show that the application of the APT on the surface of the intrinsic layer causes a change of the i-/p-interface and of the following deposited p-a-Si:H layer as well as to the electrical properties of the i-a-Si:H layer itself. Furthermore, the influence of the APT on n-i-p solar cells to the light induced degradation (LID) was studied. Dependent on the p-layer and APT depositions parameters, the results show that the application of APT leads to a higher stabilized cell performance after 1000 h light soaking compared to other cells. The influence of APT on the physical properties of the deposited materials and interfaces are discussed.